Immersive virtual reality app to promote healthy eating in children - Fuentes-Pérez, Esteban (2020)
An immersive virtual reality application was developed as a serious game to support children on their decisions about food, the system was composed by the Gear VR (Viewer and controller), and a phone which contains the mobile application developed in Unity, providing the immersive environment, the platform was based on a path where the player has to go through it choosing between different sort of meals and also between different physical activities, the effect of balanced diet plus adequate physical activity seems reflected on the avatar previously chosen by the user, the app was tested on 12 children between 8 and 10 years old during one week, children participated on the study after receiving an informed consent, analyzing the tendencies of food choice on children before and after, a notorious positive effect could be seen on the users according to the avatar analyzed at the end of the round, besides a System usability ore was also applied to evaluate the degree of usability of the app, reaching a ore of 88.33% which rates the app as very usable, this results were even better than what was planned at the beginning of the experience. © Springer Nature Switzerland AG 2020.